Supply, demand and characteristics of library Human resources in the Gaza strip, Palestine / Yaser Eilian Salama Abu Namous - Abu Namous, Yaser Eilian Salama (2014)

(untitled)
Human resource planning is important in library and information centers as a method of efficient distribution of scarce skilled labor. Libraries have given attention to human resource management of library professionals. The development of human resources needed for future planning requires a clear understanding of the levels of library personnel currently working and the need for the future strategies. This study aims to examine the current status of individuals working in the information centers in Palestine and establish staff profiles and assist in human resource staffing requirements. The study further aims to make short, medium and long-term recommendations for the development of library and information human resource centers. This study used a multiple-case design approach, involving mixed methods i.e. qualitative and quantitative approaches. The entire 380 library personnel in the library and information centers were involved in the questionnaire survey. In addition, interviews with 60 key officials were done in two phases. In the first phase, interviews were conducted and in the second phase interview after two and half years. The same officials were re-interviewed to validate and evaluate their projected information. Descriptive statistics and Chi-square test were used in the analysis and interpretation of the data. The interview and questionnaire findings indicate that the supply of libraries and information workers was deficient in number of professional staff, necessary skills such as IT and language skills. Three levels of projection, viz. high, middle, and low projections were made. A total of 90% among the concerned middle and top management said that information science programs needed to be increased. A notable finding was that that 32 respondents (53.3%) mentioned the absence of human resource development policies, plans and strategies while 25 (41.66%) indicated the current programs did not meet the needs of libraries. Respondents overall showed a significant ii difference (p < 0.005), between the job title categories, in continuing education and there is a significant difference (p < 0.001) between the gender of professionals regarding the intentions to continuing education. However, there is no significant difference (p= 0.840) when the respondents were segregated according to their ages. To address these shortcomings, a number of changes were suggested by the respondents, including academic programs to be upgraded in parallel with improvements in the curriculum, and existing staff should be given intensive training in ICT and English. They also said that salaries and incentives, work conditions and environment should be improved, and that professionals and subject specialists from other fields should be recruited. This study is important for future information resources planning in Palestine and it will contribute to a better assessment and guidelines for the future. The study also provides an approach to human resources planning for developing countries with situations similar to Palestine, as well as helping international agencies in the development of library sectors.